Adolescent borderline personality traits and dyadic behavior shape mother-adolescent cortisol synchrony - Leonie Fleck; Anna Fuchs; Stefan Lerch; Eva Möhler; Julian Koenig; Franz Resch; Michael Kaess (Borderline Personality Disorder and Emotion Dysregulation, 2023)
Abstract Background Associations between parent and child cortisol levels (“cortisol synchrony”) are often reported and positive synchrony may mark dyadic regulation on a physiological level. Although dyadic behavior during interaction and adolescent borderline personality disorder (BPD) traits are linked with individual and dyadic regulatory capacities, little is known about how both factors influence parent-adolescent cortisol synchrony. We hypothesized that cortisol synchrony would differ depending on behavioral synchrony, i.e., smooth reciprocal dyadic interaction patterns, adolescent BPD traits, and their interactions. Methods Multilevel state-trait modeling was implemented to investigate associations between concurrent mother-adolescent state cortisol and mother-adolescent average cortisol levels in a community sample of 76 mother-adolescent dyads. Three saliva samples were collected across interaction paradigms. Behavioral synchrony was observed, and adolescent BPD traits were evaluated using clinical interviews. Results First, behavioral synchrony and absence of BPD traits were linked with positive associations between adolescent and maternal state cortisol (positive synchrony), BPD traits with negative associations (negative synchrony). When interaction effects were examined, results were more nuanced. In low-risk dyads (higher behavioral synchrony, no BPD traits) asynchrony was found. When risk (BPD traits) and resource (higher behavioral synchrony) were combined, synchrony was positive. Lastly, in high-risk dyads (lower behavioral synchrony, adolescent BPD traits), negative synchrony was observed. Average adolescent and maternal cortisol levels were consistently positively associated in dyads with higher risk. Conclusions Positive dyadic interaction patterns are associated with positive state cortisol synchrony in mother-adolescent dyads and could buffer the effect of BPD traits, possibly supporting the process of physiological regulation.